Fern in Star Valley - Collins, Poppy; Potts, Pixie (London : Scholastic, 2014)
The fashion fairy princesses have been invited to their friend Fern's birthday sleepover! Princess Fern lives in the neighbouring Star Valley so, after sourcing the perfect birthday present in Sparkle City, the fairy princesses set off in suitably fashionable country gear. They arrive at Star Valley to find that Fern has created a magical campsite, complete with flower tepees, an enchanted bonfire and a delicious picnic. But after a dreamy ride on the valley's magical unicorns, they come back to find everything in disarray! Fern's little sisters, Willow and River, were so desperate to join the festivities, that they ruined the party without thinking. Luckily a bit of fairy magic and teamwork saves the sleepover, and the fairy princesses drift off to sleep under a canopy of shooting stars.
M
Formerly CIP.
b
b
Keywords: Children's stories